How can the MHC mediate social odor via the microbiota community? A deep dive into mechanisms. (18th May 2021) - Schubert, Nadine; Nichols, Hazel J; Winternitz, Jamie C
Abstract: Genes of the major histocompatibility complex (MHC) have long been linked to odor signaling and recently researchers' attention has focused on MHC structuring of microbial communities and how this may in turn impact odor. However, understanding of the mechanisms through which the MHC could affect the microbiota to produce a chemical signal that is both reliable and strong enough to ensure unambiguous transmission of behaviorally important information remains poor. This is largely because empirical studies are rare, predictions are unclear, and the underlying immunological mechanisms governing MHC–microbiota interactions are often neglected. Here, we review the immunological processes involving MHC class II (MHC-II) that could affect the commensal community. Focusing on immunological and medical research, we provide background knowledge for nonimmunologists by describing key players within the vertebrate immune system relating to MHC-II molecules (which present extracellular-derived peptides, and thus interact with extracellular commensal microbes). We then systematically review the literature investigating MHC–odor–microbiota interactions in animals and identify areas for future research. These insights will help to design studies that are able to explore the role of MHC-II and the microbiota in the behavior of wild populations in their natural environment and consequently propel this research area forward. Abstract : Determining relatedness in members of the same species through their smell can help animals cooperate with close relatives or avoid inbreeding. How genetic information is encoded in odor, and what role immune genes (MHC) and microbes play in generating odor, as well as how they interact is unclear. We outline the immune system's involvement in odor production, highlight gaps in our knowledge regarding immune gene and microbe-mediated social communication, and suggest ways to advance our understanding.